2005
DOI: 10.4141/a04-082
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Alfasure™ for the prevention and treatment of alfalfa bloat in cattle

Abstract: Efficacy of Alfasure™ for the prevention and treatment of alfalfa bloat in cattle. Can. J. Anim. Sci. 85: 111-113. Alfalfa was grazed at early stages of growth to test the efficacy of field application of the pluronic detergent Alfasure™. Bloat was prevented under optimal weather conditions in the absence of rain but heavy rains could disperse the water-soluble product. A new route of administration of Alfasure™ was also examined for the treatment of bloat. Intraruminal injection of Alfasure™ was completely ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Alfasure, a water soluble product produced in Canada, is also effective in preventing rumen bloat. Some studies have shown that intraruminal injections of the detergents Alfasure or Anti Gaz Emulsion were very effective in the treatment of grazing type rumen bloat ( 37 ). Unfortunately, the effect of these products in the prevention of feedlot bloat is not satisfactory.…”
Section: Prevention Of Feedlot Bloatmentioning
confidence: 99%
“…Alfasure, a water soluble product produced in Canada, is also effective in preventing rumen bloat. Some studies have shown that intraruminal injections of the detergents Alfasure or Anti Gaz Emulsion were very effective in the treatment of grazing type rumen bloat ( 37 ). Unfortunately, the effect of these products in the prevention of feedlot bloat is not satisfactory.…”
Section: Prevention Of Feedlot Bloatmentioning
confidence: 99%